Diseño de un helado funcional a base de frutas étnicas colombianas (2020)
Nowadays, there is a strong tendency to functional foods, due that the people are showing a great interest in their nutrition, preferring less processed, nutritious and healthier food, that provides benefits to their physical and mental health. As a result, there has been an increase in the industry in developing functional foods, that satisfies the likes and necessities of the consumer. In addition, the value and importance of products and foods that represents the country has been increasing. Therefore, the aim of this project was to formulate functional ice creams of guava, borojo and banana passionfruit, with a high antioxidant capacity provided by the fruit. Firstly, it was determined by a bibliographic research the antioxidant capacity and phenolic content of each fruit, to establish which of the fruits provides higher nutritional benefits. Afterwards, 6 different samples of ice cream were made, 2 for each fruit based on the type of the milk (cow or coconut). Measuring the overrun, melting time and carrying out a sensitive analysis, nutrition fact tables of the products and a business model. It was established that the ice creams with a greater contribution of bioactive compounds, greater global acceptability and purchase intention and low caloric content, are the ones made from banana passion fruit and guava. Also, it was concluded that the type of milk is the variable that affects significantly the overrun, as well as the fruit and type of milk affects the melting time.